AROHA SEBAGAI SARANA SOLIDARITAS SOSIAL: STUDI TENTANG TRADISI KEAGAMAAN MASYARAKAT NEGERI HENA LIMA - M. Syafin Soulisa (DIALEKTIKA, 2018)
The religion believed by adherents are not limited in the form of an offering to God, but religion also has a strong sense of attachment solidarity for fellow adherents. Sense of community and solidarity that has always embodied by its followers in the form of rituals and religious ceremonies. This study aims to determine the implementation process Aroha ceremony tradition as a form of social solidarity implemented by the State society Hena Lima. In analyzing the data, the authors use qualitative methods, analytical techniques which use descriptive qualitative research that generates data in the form of words written or spoken of people and behaviors that can be observed, with the aim to describe the state of the research objectives according to what existence, as obtained in the study. Based on the results of research conducted on the social solidarity of State Hena Five embodied in the tradition of Aroha lumatau dati, overall it can be concluded that Aroha tradition has become a religious tradition for generations carried out by the State society Hena Five each coming month of Rabi al-Awwal or called by month Maulud. Implementation process by gathering all the clans Lumatau Dati in the bonds of solidarity among children and grandchildren lumatau dati